Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Guru Melalui Disiplin Kerja - Nina Suyatni; Tin Agustina Karnawati; Fathorrahman (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE INFLUENCE OF WORK MOTIVATION AND WORK ENVIRONMENT ON TEACHER PERFORMANCE THROUGH WORK DISCIPLINE This study aims to analyze the influence of work motivation and work environment on teacher performance, with work discipline as an intervening variable. The research involved 30 teachers at Tiara Nusa Permata Education Foundation in Palembang, selected using a saturated sampling technique. A quantitative approach was employed, with data collected using a Likert-scale questionnaire and analyzed through the Partial Least Square (PLS) method. The results show that both work motivation and work environment have a positive and significant effect on teacher performance. They also significantly influence work discipline. Work discipline significantly mediates the relationship between work environment and teacher performance, but does not significantly mediate the relationship between work motivation and teacher performance. These findings suggest that fostering a supportive work environment and building disciplined behavior are key strategies for improving teacher performance. The results can serve as a basis for formulating human resource management policies in private educational institutions.